Is the valuation of an insurance company specific? - LEVYNE, OLIVIER; HELLER, DAVID (Bankers, Markets & Investors, 2025)
Valuation is traditionally based on listed peers approaches and DCF for corporate entities. Most aggregates such as EBITDA and EBIT are not relevant for insurance companies and can’t therefore be the foundations of their valuations. Given the reliance of insurance companies’ operating activity on the Solvency 2 regulation, their valuation must include such a constraint. This is why the peers approach is focused on multiples of book value of equity (P/BV) and net income (P/E). Moreover, a ROE correlated P/BV enables to reconcile both approaches. The main intrinsic approach is based on dividend discount model, the dividend corresponding to the excess equity taking the solvency constraint into account. An empirical study based on 17 European insurance companies’ evidences that the listed peers approach generally explains the market capitalisation whereas intrinsic approaches, based on a limited set of information, provide values which are a bit higher. In that context, as recommended by a paper dated from 2013 and focussed on valuation on US banks, the listed peers approach has to be the central approach for European insurance companies.